Mastering Autodesk Revit 2018 - Kirby, Lance (John Wiley & Sons, 2018)
This book will help you to take the basics of Revit and BIM that you already know and expand on them using real-world examples. We will show you how to take a preliminary model an add layers of intelligence to help analyze and augument your Designs. We'll show you how to create robust and accurature documentation, and then we'll hepl you through the construction process.....